Eksplorasi Strategi Guru PAUD dalam Menghadapi Tuntutan Calistung dari Orang Tua: Studi Kasus di TK Islam Bina Taqwa - Hodeniah; Baik Nilawati Astini; Syaiful Musaddat (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This research was motivated by parental demands for early childhood literacy and numeracy learning before entering elementary school. This study aims to determine the strategies of early childhood education teachers in dealing with parental demands for literacy and numeracy and their impact on the development of children's literacy and numeracy skills at Bina Taqwa Islamic Kindergarten. This study used a qualitative approach with a case study research type. The research subjects consisted of class teachers, principals, and parents. Data collection techniques were carried out through observation, interviews, and documentation, analyzed through data reduction, data presentation, and drawing conclusions. The results showed that teachers implemented various strategies, namely communication and education with parents, integration of literacy and numeracy learning through play activities, the application of the ATIK learning model, routine activities, literacy and numeracy environments, and collaboration between teachers and institutions. These strategies have an impact on the development of children's literacy and numeracy skills as demonstrated by the ability to recognize letters and numbers, simple number sequences, increased vocabulary through storytelling activities, starting to read simple words, and increasing children's interest and motivation to learn. However, several obstacles were still found, such as differences in children's abilities, parental involvement, and the risk of academic stress if the learning provided is not appropriate to the child's developmental stage. Therefore, learning to read, write, and count for early childhood needs to be done in stages, in a fun way, and in accordance with PAUD principles.